MicroRNA as Biomarkers and Diagnostics. Issue 1 (January 2016) - Wang, Jin; Chen, Jinyun; Sen, Subrata
<x xml:space="preserve">Abstract</x> MicroRNAs (miRNAs) are a group of small non‐coding RNAs that are involved in regulating a range of developmental and physiological processes; their dysregulation has been associated with development of diseases including cancer. Circulating miRNAs and exosomal miRNAs have also been proposed as being useful in diagnostics as biomarkers for diseases and different types of cancer. In this review, miRNAs are discussed as biomarkers for cancer and other diseases, including viral infections, nervous system disorders, cardiovascular disorders, and diabetes. We summarize some of the clinical evidence for the use of miRNAs as biomarkers in diagnostics and provide some general perspectives on their use in clinical situations. The analytical challenges in using miRNAs in cancer and disease diagnostics are evaluated and discussed. Validation of specific miRNA signatures as biomarkers is a critical milestone in diagnostics. J. Cell. Physiol. 230: 25–30, 2016. © 2015 Wiley Periodicals, Inc.